2018
DOI: 10.1177/1046878117753498
|View full text |Cite
|
Sign up to set email alerts
|

Grim FATE: Learning About Systems Thinking in an In-Depth Climate Change Simulation

Abstract: Background. Simulations of complex systems have a long history of use for the study and promotion of systems thinking, yet more can be done in identifying games that promote development of systems thinking. Aim. This study is an exploration of the hypothesis that FATE OF THE WORLD, a challenging and complex climate change simulation, can promote systems thinking about climate change. Questions. This article analyzes players’ engagement with FATE OF THE WORLD using three key questions: 1. In what ways does the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Overall, our findings add to the growing body of research suggesting that educational games constitute a promising and novel way of learning (Wouters et al, 2013), also mirroring the research done by previous sustainability researchers utilizing games (e.g., Schaal et al, 2018;Waddington and Fennewald, 2018). One of the central findings from our study is that Eco has been shown to reinforce and contextualize our respondents' overall level of environmental literacy and systems thinking.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Overall, our findings add to the growing body of research suggesting that educational games constitute a promising and novel way of learning (Wouters et al, 2013), also mirroring the research done by previous sustainability researchers utilizing games (e.g., Schaal et al, 2018;Waddington and Fennewald, 2018). One of the central findings from our study is that Eco has been shown to reinforce and contextualize our respondents' overall level of environmental literacy and systems thinking.…”
Section: Discussionsupporting
confidence: 82%
“…Enjoying environmental gameplay is theorized to have a significant effect on the subsequent learning outcomes from playing (Fjaellingsdal and Klöckner, 2017), thus lending support to the study's findings. Another study revealed that individuals who played Red Redemption's Fate of the World, a simulation revolving around a 200-year period of societal and environmental impacts (Klöckner, 2015, p. 198), showed a higher degree of environmental systems thinking than a control group (Waddington and Fennewald, 2018). Systems thinking -the ability to understand the complexity of all the individual parts of an interconnected system (Aronson, 1996) -is crucial in the understanding of ecosystems.…”
Section: The Effectiveness Of Game-based Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Most soft OR university courses are found in a geographically limited area (i.e., UK), so it is not surprising that soft OR has not reached a critical mass of users to gain widespread usage within the global OR community (Mingers, 2009(Mingers, , 2011. There does exist educational trainers (Waddington and Fennewald, 2018), but these are limited in number. Without the necessary soft OR educational courses being readily available, "there is a powerful argument that training young OR analysts only in (mathematical) techniques, without giving them an awareness of realities of the organizational and management contexts [i.e., problem structuring], are doing them a huge disservice" (Mingers, 2011).…”
Section: Valuementioning
confidence: 99%